Systems prediction of chronic lung allograft dysfunction: Results and perspectives from the Cohort of Lung Transplantation and Systems prediction of Chronic Lung Allograft Dysfunction cohorts - Pison, Christophe; Tissot, Adrien; Bernasconi, Eric; Royer, Pierre-Joseph; Roux, Antoine; Koutsokera, Angela; Coiffard, Benjamin; Renaud-Picard, Benjamin; Le Pavec, Jérôme; Mordant, Pierre; Demant, Xavier; Villeneuve, Thomas; et al. (Frontiers in Medicine, 2023)
Background: Chronic lung allograft dysfunction (CLAD) is the leading cause of poor long-term survival after lung transplantation (LT). Systems prediction of Chronic Lung Allograft Dysfunction (SysCLAD) aimed to predict CLAD paving the way to preventive and/or early interventions. Methods: To predict CLAD, we investigated in parallel the clinicome; the exposome; the immunome; genome polymorphisms; blood transcriptome; plasma proteome studies and assessment of MSK1 expression. Results: Clinicome: the best multivariate logistic regression analysis model for early-onset CLAD in 422 LT eligible patients generated a ROC curve with an area under the curve of 0.77 where Donor Specific Antibodies were the strongest predictors. Exposome: chronic exposure to air pollutants appears deleterious on lung function levels in LT recipients (LTRs), might be modified by macrolides, and increases mortality. Our findings established a link between the lung microbial ecosystem, human lung function, and clinical stability post-transplant. Immunome: a decreased expression of CLEC1A in human lung transplants is predictive of the development of chronic rejection and associated with a higher level of interleukin 17A; immune cells support airway remodelling through the production of plasma MMP-9 levels, a potential predictive biomarker of CLAD. Blood CD9-expressing B cells appear to favor the maintenance of long-term stable graft function and is a potential new predictive biomarker of BOS-free survival. An early increase of blood CD4+CD57+ILT2+ T cells after LT may be associated with CLAD onset. Genome: Donor Club cell secretory protein G38A polymorphism is associated with a decreased risk of severe primary graft dysfunction after LT. Transcriptome: blood POU class 2 associating factor 1, T-cell leukemia/lymphoma domain, and B cell lymphocytes, were validated as predictive biomarkers of CLAD phenotypes more than 6 months before diagnosis. Proteome: blood A2MG is an independent predictor of CLAD, and MSK1 kinase overexpression either a marker or a potential therapeutic target in CLAD. Conclusion: Our ambition, partially achieved, was to predict CLAD as early as possible before any decline in lung function and/or clinical manifestations. Replication has not always been carried out. A dynamic full handprint derived with the potential to predict graft fate, still needs to be calibrated and validated.